Elite sport - return to domestic competition guidance (2020)
The following guidance covers Stage Three of the proposed five stage framework for returning to full unrestricted elite sporting competition and has been produced by a working group of leaders, Chief Medical Officers and partner organisation representatives across Olympic, Paralympic and professional sports in collaboration with the DCMS, PHE, DHSC and UK Sport.